Comparative clinical utility of once-weekly subcutaneous abatacept in the management of rheumatoid arthritis - Rakieh C; Conaghan PG (Therapeutics and Clinical Risk Management, 2014)
Chadi Rakieh, Philip G ConaghanLeeds Institute of Rheumatic and Musculoskeletal Medicine, University of Leeds, NIHR Leeds Musculoskeletal Biomedical Research Unit, Leeds, UKAbstract: Biologic therapies in rheumatoid arthritis are now part of standard practice for disease that proves difficult to control with conventional disease-modifying anti-rheumatic drugs. While anti-tumor necrosis factor therapies have been commonly used, other targeted biologic therapies with different mechanisms of action are becoming increasingly available. Abatacept is a recombinant fusion protein that inhibits the T-cell costimulatory molecules required for T-cell activation. Intravenous abatacept has good clinical efficacy with an acceptably low toxicity profile in rheumatoid arthritis, but the subcutaneous mode of delivery has only recently become available. In this article, we examine key efficacy and safety data for subcutaneous abatacept in rheumatoid arthritis, incorporating evidence from five large Phase III studies that included people with an inadequate response to methotrexate and an inadequate response to biologic disease-modifying anti-rheumatic drugs. The results demonstrate that subcutaneous abatacept has efficacy and safety comparable with that of intravenous abatacept and adalimumab. In addition, inhibition of radiographic progression at year 1 in relatively early rheumatoid arthritis is consistent with that of adalimumab. Subcutaneous abatacept is well tolerated, with very low rates of discontinuation in both short-term and long-term follow-up.Keywords: rheumatoid arthritis, therapy, abatacept, T-cell